Educational and employment outcomes associated with childhood traumatic brain injury in Scotland: A population-based record-linkage cohort study - Meghan Visnick; Jill Pell; Daniel Mackay; David Clark; Albert King; Michael Fleming (International Journal of Population Data Science, 2023)
Objectives Traumatic brain injury (TBI) is a leading cause of death and disability among young children and adolescents and the effects can be lifelong and wide-reaching. This study aimed to compare the educational and employment outcomes of Scottish schoolchildren previously hospitalised for TBI with their peers.